Impact of Multi-Component Intervention On Selected Behavioural Problems Among School Going Adolescents - K, Shija; Nambi, Shanthi; Indira, Sreeja; Vijayaraghavan, R. (Journal of Neonatal Surgery, 2025)
Introduction: Adolescence is a pivotal period of development in one’s life. There is a need of adaptation in emotional and social behaviour and adoption of healthy patterns in sleep, exercise, coping, problem solving and interpersonal skills. Behavioural disorders in younger adolescents like hyperactivity and conduct problems can affect the studies and add a risk of criminal and anti- social behaviour. These behavioural problems along with smartphone addiction in this age group may become a challenge to the society, if not addressed properly. This study aims to evaluate the impact of a multi-component intervention (MCI) on emotional-behavioural problems (EBP) like hyperactivity, conduct disorder, peer relationship problems and smartphone addiction among the adolescents of 13-16 years. Methods: A quasi- experimental design was used to find the impact of multi-component intervention (MCI) on behavioural problems of adolescents. After obtaining a voluntarily signed informed consent, and ensuring confidentiality, Strengths and Difficulties Questionnaire (SDQ11-17) was administered to 804 school going adolescents from different schools of Thiruvananthapuram District of Kerala (South India) to identify those with behavioural problems, based on the specified tool. Socio- demographic data sheet was used to collect the adolescent’s characteristics; with the second section of, Smartphone Addiction Scale – Shortened version (SAS-SV). Data in this phase was analyzed using SPSS version 20. Among the 804 adolescents, 214 who met the criteria for EBP were chosen and were assigned to control and experimental groups (108 and 106 respectively). Then MCI consisted of online psycho education, pranayama and aerobic exercise with dancing steps was given to the experimental group for 10weeks and post test was done for both the groups. Data were analysed by two way repeated measures analysis of variance (RM-ANOVA) with Boneferoni ‘t’ test for multiple comparisons and one-way Kruskal Wallis ANOVA on ranks with Dunn’s multiple comparison test. Results: The results showed that there was a significant impact of multi-component intervention in reducing the behavioural problems like hyper activity, conduct problems and peer problems among experimental group in comparison to the control (p< 0.001). Conclusion: The study shows the positive effect of multi component intervention to manage behavioural problems, if regularly practised.